STRATEGIC DEVELOPMENT OF THE NATIONAL ECONOMY THROUGH THE PRISM OF THE GDP ANALYSIS METHODOLOGY - Костюнік, Олена; Щепіна, Тетяна (SWorldJournal, 2024)
During the period of martial law, Ukraine implements a number of development strategies to achieve sustainable economic growth at both the national and regional levels, especially those regions that have experienced catastrophic destruction. Notes the la